2015
DOI: 10.4172/2161-0932.1000346
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Severity is Affected by T the Lipid Profile in Egyptian Patients

Abstract: According to world psoriasis day consortium about 125 million people all over the world suffer from this disease, however, in some countries there is a higher prevalence rate of psoriasis, as in Kazakhstan,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…Studies done in recent years have shown a significant increase in TC, TAG, LDL, very low-density lipoprotein, and decrease in HDL in psoriasis patients as compared to non-psoriatic controls. 23 26 The HDL-cholesterol was significantly decreased in our study, which is in agreement with previous studies, whereas Javidi et al, in his study, reported no difference in HDL level between psoriasis patients and controls. 27 We did not find significant changes in the rest of the lipid profile like TC, TAG, and LDL, which is quite opposite to the findings of previous research.…”
Section: Discussionsupporting
confidence: 93%
“…Studies done in recent years have shown a significant increase in TC, TAG, LDL, very low-density lipoprotein, and decrease in HDL in psoriasis patients as compared to non-psoriatic controls. 23 26 The HDL-cholesterol was significantly decreased in our study, which is in agreement with previous studies, whereas Javidi et al, in his study, reported no difference in HDL level between psoriasis patients and controls. 27 We did not find significant changes in the rest of the lipid profile like TC, TAG, and LDL, which is quite opposite to the findings of previous research.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with many earlier reports [6,8,9]. Further the elevations in plasma lipid parameters observed in present study in psoriasis patients as well as in clinically sub grouped psoriasis patients is in agreement with studies of Mohammed Amer et al, [33].…”
Section: Resultssupporting
confidence: 94%
“…These findings do not match with previous studies conducted on psoriasis patients. They reported the higher total cholesterol, LDL and triglyceride levels and lower HDL levels in psoriasis patients compared with that of control group [11][12][13][14][15] . Elevated serum total cholesterol and triglyceride levels were also demonstrated in patients with pemphigus compared with controls.…”
Section: Discussionmentioning
confidence: 97%